Planning and scheduling of CO2 capture, utilization and storage (CCUS) operations as a strip packing problem - Tapia, John Frederick D.; Lee, Jui-Yuan; Ooi, Raymond E.H.; Foo, Dominic C.Y.; Tan, Raymond R. (Process safety and environmental protection, 2016)
[Display omitted] •Two MILP models are developed for CCUS planning and scheduling.•Both models use strip packing as a geometric analog for time and flow aspects.•Model 1 deals with scheduling EOR operations.•Model 2 deals with source–sink matching for CO2 storage. CO2 capture, utilization and storage (CCUS) is an important carbon management strategy that involves capturing CO2 from flue gas, transporting it, utilizing it for economically productive activities (carbon capture and utilization, or CCU), and/or permanently disposing it in non-atmospheric sinks (carbon capture and storage, or CCS). Some technologies, such as enhanced oil recovery (EOR) allow simultaneous CCUS, while other alternatives are either purely CCS (e.g., geological storage) or purely CCU (e.g., use of CO2 as a process plant feedstock). In this work, CCUS is addressed in the context of a large-scale CO2 chain that contains both CCS and CCU options. It is necessary to consider the availability of CO2 sources and sinks to develop a profitable allocation plan for such CCUS systems. Thus, a modeling framework using a geometric representation is proposed to optimize both scheduling and allocation in a CCUS system, given multiple CO2 sources and sinks. Two mixed integer linear programming (MILP) models are developed to address three important factors for planning downstream CCUS operations, i.e., scheduling of CO2 capture and EOR operations, allocation of CO2 supply for EOR operations, and source–sink matching subject to injectivity and capacity constraints. Two case studies are then solved to illustrate the two MILP models.